Architecture and key techniques of parallel creation through the fusion of human-cyber-physical intelligence in CPSS - Chao GUO; Yue LU; Xiao WANG; Da YI; Xiao WANG; Fei-Yue WANG (智能科学与技术学报)
With the expansion of the fields covered by AI, artistic creation will become the next hot spot for AI research and applications.Building a metaverse with diverse styles, realistic contents, flexible strokes and accurate descriptions based on parallel system theory and ACP approach will provide a feasible way to improve AI creation capability.The intelligence of human, AI, and robots were fused to develop a parallel creation architecture through the creation by AI, the evaluation by humans, and the execution by robots.The parallel creation with the key methods of style transfer, content combination, stroke generation and image captioning in computational experiments were explained.The parallel creation system was validated through the painting experiments.The parallel creation system will improve the creation capability of artificial intelligence in cyberspace and physical space, and promote the human-cyber-physical collaborative creation through the fusion of them.